Structure and function of secretory glochids and nectar composition in two opuntioideae (Cactaceae) species - Silva, Stefany Cristina de Melo [UNESP]; Machado, Silvia Rodrigues [UNESP]; Nepi, Massimo; Rodrigues, Tatiane Maria [UNESP] (Canadian Science Publishing, 2020)
Cactaceae exhibit highly modified spines that are considered to be extrafloral nectaries (EFNs). Despite their ecological and taxonomical relevance in this family, little is known on their structure and function. We have described the anatomy, ontogenesis, and ultrastructure of the secretory glochids in two Opuntioideae species. Young cladodes of Brasiliopuntia brasiliensis (Willd.) A. Berger and Nopalea cochenillifera (L.) Salm-Dyck were processed for light and electron microscopy studies. The composition of the secretions was analyzed by high performance liquid chromatography. The secretory glochids were soft, massive, and barbed, as well as translucent. Hyaline droplets on the secretory glochid apex were collected by aggressive ants. The secretory glochids originated from the areolar meristem, beginning as small protuberances formed by protoderm and ground meristem. Mature secretory glochids consisted of a central multiseriate axis of ground cells covered by uniseriate epidermis with a continuous cuticle, and exhibited three regions: (i) dilated vascularized base with parenchyma cells exhibiting features associated to nectar secretion; (ii) elongated median region with juxtaposed fusiform non-lignified parenchyma cells; and (iii) tapered apical portion with immature fibers loosely arranged cells. The exudate was sucrose-dominant with a similar amino acid profile in both species. Our results shed light on the secretory activity of glochids in Cactaceae and their role in cactus–ant interactions.
Keywords: Anatomy; Brasiliopuntia brasiliensis; Cactus; Nectar; Nopalea cochenillifera; Secretory spines; Ultrastructure